Introduction to the Special Issue: Operationalising Social Science for Epidemic Response. Issue 1 (1st March 2022) - Schmidt-Sane, Megan; Grant, Catherine; Ripoll, Santiago; Hrynick, Tabitha; Abbas, Syed
Abstract : This special issue of Anthropology in Action presents a collection of articles that reflect on and analyse the role of social science in epidemic response. The COVID-19 pandemic has exposed deep social and economic inequalities within and across countries which produce unequal COVID-19 outcomes. Researchers have long noted the connections between socio-economic inequalities and infections, and there is growing recognition that epidemics are also social and political events (Bardosh et al. 2020). Anthropological and other social science research has contributed to epidemic response, through attention to cultural and politico-economic context, reframing community 'resistance', bolstering community engagement in preparedness and response, and informing response activities, including risk communication (Abramowitz 2017; Bardosh et al. 2020). Despite this, much of the work has been ad hoc and not systematically integrated into the systems of epidemic response, with the exception of the Centres d'Analyses des Sciences Sociales (CASS) in the Democratic Republic of Congo (DRC). This special issue is timely, in that it builds on foundational work in social science and epidemic response, draws on tensions and experience from recent epidemics including COVID-19 and Ebola, and charts a way forward at both a theoretical and a practical level.